2019
DOI: 10.3390/f10050452
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Horizontal Accuracy, Shape Similarity and Cost of Three Different Road Mapping Techniques

Abstract: Accurate spatial information on forest roads is important for forest management and harvest operations. This study evaluated the positional accuracy, shape similarity, and cost of three mapping techniques: GNSS (Global Navigation Satellite System) mapping, CAD file conversion (as-built drawing), and image warping. We chose five road routes within the national forest road system in the Republic of Korea and made digital road maps using each technique. We then compared map accuracy to reference maps made from fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The results showed that the VIM-V presented a high level of reliability in detecting the perturbations. • Kweon et al (2019) applied the SBOM to assessing the positional accuracy of three different road-mapping techniques (CAD file conversion, image warping and GNSS mapping). The XL lines were composed of five routes of about 6 km.…”
Section: Applications and Resultsmentioning
confidence: 99%
“…The results showed that the VIM-V presented a high level of reliability in detecting the perturbations. • Kweon et al (2019) applied the SBOM to assessing the positional accuracy of three different road-mapping techniques (CAD file conversion, image warping and GNSS mapping). The XL lines were composed of five routes of about 6 km.…”
Section: Applications and Resultsmentioning
confidence: 99%
“…Three methods were used to assess the results of geometry of footprint building extraction, which were segment of line comparison, shape index similarity (Veltkamp and Hagedoorn, 2000;Veltkamp, 2011b;Kweon et al, 2019), and edge point-correspondence (Ramirez and Ali, 2003;Kweon et al, 2019). The segment of line comparison was used to evaluate the number of sections of every line resulted from samples against reference dataset.…”
Section: Building Extraction Analysismentioning
confidence: 99%
“…If the shape is circular, the shape index is 1 (i.e., the smallest perimeter in a given internal area). If the shape is a square, the shape index is 1.13 [16]. The shape index can be expressed by Equation (2).…”
Section: Factors Affecting the Forest Road Circuitymentioning
confidence: 99%
“…However, in the case of non-urbanized areas, the deviation may be large [1,15]. In particular, forest roads, which provide infrastructure for sustainable forest management [16], are affected by their route alignments due to mountainous terrain; thus, most of the route is composed of complex linear shapes, and the circuity factors deviate considerably from region to region [11,15]. To estimate the actual road distance for planning a road network or forest operation, estimating the network distance and calculating the circuity factor of the forest road network are necessary.…”
mentioning
confidence: 99%